Dynamics between macro-economic variables and the stock market: Evidence from India - Bhardwaj, Nikhil; Sharma, Nishi; Mavi, Anupreet Kaur (Asian Journal of Economic Modelling, 2023)
The present paper examines the dynamics between macroeconomic variables and the stock market. The index of industrial production, inflation, gold price, oil price, and return from treasury bills have been used as proxy macroeconomic variables. The Indian stock market has been typified by the Sensex. Monthly observations have been analyzed from April 1993 to October 2022 through cointegration and the Granger causality test to examine possible long-run and short-run relationships, respectively. The results proclaim the presence of cointegration among variables. Further, the analysis of normalized cointegrating coefficients reveals that in the long run, changes in inflation and the rate of return from T-bills positively affect the stock market. While changes in gold and oil prices have a negative impact on the stock market. The Granger causality test implies that in the short run, the stock market is sensitive to changes in the index of industrial production, inflation, and oil prices. The results are expected to be fruitful for investors as well as traders when designing their investment and trading strategies. Since the results indicate that volatility in the stock market can significantly affect industrial production, inflation, and gold prices, regulators should be vigilant about perturbations in the stock market to mitigate adverse effects.